TOPLUMSAL KÜLTÜRÜN GENÇLERİN GİRİŞİMCİLİK EĞİLİMİNE ETKİSİ - KOÇ, BARANSEL (Fırat Üniveristesi, 2016)
Bu çalışmanın amacı üniversitede eğitim gören öğrencilerin kültürel özellikleri ile girişimcilik eğilimleri arasındaki ilişkiyi incelemektir. Araştırmada Fırat Üniversitesi'nde eğitim gören 490 öğrencinin toplumsal kültür özellikleri ve girişimcilik eğilimleri ölçülmüştür. Gençlerin girişimcilik eğilimlerinin olması gerek bölge gerekse ülke ekonomisinin gelişmesi açısından önemlidir. Bu durum da gençlerin toplumsal kültür özellikleri, onların girişimcilik eğilimleri üzerinde oldukça etkilidir. Araştırmada Toplumsal Kültür Ölçeği ve Girişimcilik Eğilimleri Ölçeği kullanılmıştır. Verilerin analizinde ise; güvenilirlik ve geçerlilik analizleri, frekans analizi, korelasyon ve regresyon analizi, bağımsız örneklem t testi, tek yönlü varyans analizi, tukey ve lsd testlerinden yararlanılmıştır. Araştırma sonucunda öğrencilerin toplumsal kültür özellikleri alt boyutları olan belirsizlikten kaçınma, güç mesafesi, erillik-dişilik, denetim noktası ve bireycilik-toplumculuk ile girişimcilik eğilimleri arasında anlamlı bir ilişkinin olduğu; öğrencilerin toplumsal kültür özelliklerinin ve girişimcilik eğilimlerinin, öğrencilerin demografik özelliklerine göre farklılık gösterdiği saptanmıştır

The aim of this study is to analyze the relationship between the cultural characteristics of the graduate students and their inclination for entrepreneurship. In the study, 490 students of Fırat University have been examined with regard to their social culture characteristics and their inclination for entrepreneurship. The youth's inclination for entrepreneurship is crucial both for regional and national economic improvement. In this manner, youth's social culture characteristics are considerably important for their inclination for entrepreneurship. In the study, Social Culture Scale and Inclination for Entrepreneurship Scale have been utilized. In the analyses of the data, reliability and validity analyses, frequency analyze, correlation and regression analyze, independent sample test, unilateral variance analyze, tukey and lsd tests have been benefited. As the results of the research, it has been found out that there was a significant relationship between the sub-dimensions of social culture such as avoiding uncertainty, power distance, masculinity and femininity, auditing point, and individualism and sociability, and that the students' social culture characteristics and their inclination for entrepreneurship have been differentiating according to their demographic features.
The effect of the social culture on youth's inclination for entrepreneurship
Keywords: İşletme